Health promotion in a pediatric clinic: experiences of nursing students (Research, Society and Development, 2021)
Describe the care experience lived with hospitalized children from play therapy. This is a descriptive study of the experience report type, developed from the experiences of nursing students, permeated by the activities of the Module of Interdisciplinary Practices in Teaching, Research and Extension II - PIEPE II, of the Nursing Course at Universidade Estadual Vale do Acaraú - UVA. They were carried out from May to July 2019, in the pediatrics of Hospital Santa Casa de Misericórdia, located in the municipality of Sobral, state of Ceará. The performed interventions were carried out in seven meetings and in the application of the interventions, each academic built a different character to present themselves in the actions and approach the themes in a playful way. The result of the interventions was evaluated according to the interaction and enthusiasm of the children during the dynamics. To start the process of interventions, the academics made a previous visit to the Pediatrics Sector to see the children's situational reality. In view of this, it is noted that play therapy was satisfactory, as it favored effective communication, the formation of a bond between professional-patient and enabled comprehensive and humanized care. The experience provided a view beyond theory, adding values ​​in academic training on the relevance of holistic and humanized care that must be worked with the patient, especially the child.